Employees’ Perception of the Effectiveness of Togetherness Activities in Strengthening Spiritual Bonding at Bank Indonesia, North Maluku - Santrillah Nasir; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze employee perceptions of the effectiveness of togetherness activities in strengthening spiritual bonding, identify the factors that influence it, and understand the efforts made by the organization and employees at Bank Indonesia, North Maluku Province. This study used a qualitative method with a descriptive approach through interviews, observation, and documentation techniques. The results showed that employee perceptions of togetherness activities were considered positive and effective in strengthening spiritual bonding, which was reflected in an increased sense of togetherness, kinship, and emotional connectedness among employees. Diverse and flexible activities were able to create comfortable and meaningful interactions. Factors that influenced the effectiveness of activities included driving factors such as the role of leadership and internal employee motivation, inhibiting factors such as limited time and workload, and supporting factors such as a culture of togetherness and consistency in activity implementation. Efforts to increase effectiveness were carried out through structured programs, improving the quality of activities, providing motivation, and active employee participation in building social interactions. Thus, togetherness activities play an important role in building a harmonious, productive, and spiritually based work environment. Keywords: spiritual bonding, togetherness activities, employee perceptions, effectiveness